2007
DOI: 10.1002/cm.20203
|View full text |Cite
|
Sign up to set email alerts
|

Cortical actin filament organization in developing and functioning stomatal complexes of Zea mays and Triticum turgidum

Abstract: Cortical actin filament (AF) organization was studied in detail in developing stomatal complexes of the grasses Zea mays and Triticum turgidum. AF arrays during the whole stomatal complex development are dynamic, partly following the pattern of cortical microtubule (MT) organization. They also exhibit particular patterns of organization, spatially and temporarily restricted. Among AF arrays, the radial ones that underlie young guard cell (GC) periclinal walls, those that line the bulbous GC ends and the AF rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 48 publications
5
47
0
Order By: Relevance
“…It is well accepted that the microfilament cytoskeleton is strongly linked to these microtubule structures during cell division, although subtle differences in microfilament distribution have been identified (Panteris, 2008). While some studies have shown that microfilaments codistribute with microtubules in the preprophase band (Kakimoto and Shibaoka, 1987;Palevitz, 1987;Traas et al, 1987;Zachariadis et al, 2001Zachariadis et al, , 2003, others have shown that cortical actin filaments do not always follow the pattern of the preprophase microtubule band Wick, 1990, 1991;Panteris et al, 1992Panteris et al, , 2007Collings and Wasteneys, 2005). In the mitotic spindle, microfilaments are usually present (Schmit and Lambert, 1987;Seagull et al, 1987;Traas et al, 1987;Lloyd and Traas, 1988;Panteris et al, 1992;Cleary, 2001;Collings et al, 2001), but their absence from the spindle has also been reported (Liu and Palevitz, 1992;Baluska and Hasenstein, 1997;Vitha et al, 2000;Voigt et al, 2005).…”
Section: Afh14 Plays An Important Role In Cell Divisionmentioning
confidence: 99%
“…It is well accepted that the microfilament cytoskeleton is strongly linked to these microtubule structures during cell division, although subtle differences in microfilament distribution have been identified (Panteris, 2008). While some studies have shown that microfilaments codistribute with microtubules in the preprophase band (Kakimoto and Shibaoka, 1987;Palevitz, 1987;Traas et al, 1987;Zachariadis et al, 2001Zachariadis et al, , 2003, others have shown that cortical actin filaments do not always follow the pattern of the preprophase microtubule band Wick, 1990, 1991;Panteris et al, 1992Panteris et al, , 2007Collings and Wasteneys, 2005). In the mitotic spindle, microfilaments are usually present (Schmit and Lambert, 1987;Seagull et al, 1987;Traas et al, 1987;Lloyd and Traas, 1988;Panteris et al, 1992;Cleary, 2001;Collings et al, 2001), but their absence from the spindle has also been reported (Liu and Palevitz, 1992;Baluska and Hasenstein, 1997;Vitha et al, 2000;Voigt et al, 2005).…”
Section: Afh14 Plays An Important Role In Cell Divisionmentioning
confidence: 99%
“…This protein also accumulates at definite regions of subsidiary cells and intervening cells of stomatal rows of Z. mays, 57,58 where distinct AF accumulations have also been found. 34,58 Thus, the AF-patches at the polar end of Z. mays SMCs, should not be considered as prime polarizing factors, since they are absent from SMCs in other grasses like Triticum turgidum, but they may be related to the local SMC bulging toward the inducing GMC. 12,34 Evidence favoring this hypothesis is that in TIBA-and LY294002-treated SMCs, where the polar nucleus migration and the asymmetrical division were inhibited, AF-patches were assembled.…”
Section: Auxin Signaling and Induction Of Smc Divisionmentioning
confidence: 99%
“…34,58 Thus, the AF-patches at the polar end of Z. mays SMCs, should not be considered as prime polarizing factors, since they are absent from SMCs in other grasses like Triticum turgidum, but they may be related to the local SMC bulging toward the inducing GMC. 12,34 Evidence favoring this hypothesis is that in TIBA-and LY294002-treated SMCs, where the polar nucleus migration and the asymmetrical division were inhibited, AF-patches were assembled. Moreover, in auxintreated leaves, in which SMC polarization and asymmetrical division is expanded into protodermal regions close to leaf base, AFpatch was only detected in SMCs bulging toward their adjacent GMCs.…”
Section: Auxin Signaling and Induction Of Smc Divisionmentioning
confidence: 99%
See 2 more Smart Citations